Synchrotron X-ray fluorescence microscopy-enabled elemental mapping illuminates the 'battle for nutrients' between plant and pathogen. (13th January 2021) - Naim, Fatima; Khambatta, Karina; Sanglard, Lilian M V P; Sauzier, Georgina; Reinhardt, Juliane; Paterson, David J; Zerihun, Ayalsew; Hackett, Mark J; Gibberd, Mark R
Abstract: Metal homeostasis is integral to normal plant growth and development. During plant–pathogen interactions, the host and pathogen compete for the same nutrients, potentially impacting nutritional homeostasis. Our knowledge of outcome of the interaction in terms of metal homeostasis is still limited. Here, we employed the X-ray fluorescence microscopy (XFM) beamline at the Australian Synchrotron to visualize and analyse the fate of nutrients in wheat leaves infected with Pyrenophora tritici-repentis, a necrotrophic fungal pathogen. We sought to (i) evaluate the utility of XFM for sub-micron mapping of essential mineral nutrients and (ii) examine the spatiotemporal impact of a pathogen on nutrient distribution in leaves. XFM maps of K, Ca, Fe, Cu, Mn, and Zn revealed substantial hyperaccumulation within, and depletion around, the infected region relative to uninfected control samples. Fungal mycelia were visualized as thread-like structures in the Cu and Zn maps. The hyperaccumulation of Mn in the lesion and localized depletion in asymptomatic tissue surrounding the lesion was unexpected. Similarly, Ca accumulated at the periphery of the symptomatic region and as microaccumulations aligning with fungal mycelia. Collectively, our results highlight that XFM imaging provides the capability for high-resolution mapping of elements to probe nutrient distribution in hydrated diseased leaves in situ . Abstract : Synchrotron X-ray fluorescence microscopy elemental maps highlight major nutrient re-distribution during disease progression.